Pelatihan Digitalisasi Pembukuan Menggunakan Credibook Pada UMKM Tahu Tempe UD. Sumber Hidup - Purnama, Ita; Arlin, Wulan; Pasha, Naurah Islami (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Training on the use of Credibook digital technology was conducted to improve financial management capacity in micro, small, and medium enterprises (MSMEs) producing tofu and tempeh in UD. Source of Livelihood in Bima City. The training aims to provide a comprehensive understanding of how to utilize the main features of the application, such as transaction recording, inventory management, monitoring of receivables and payables, and the automatic generation of financial reports. The implementation methods included a needs assessment phase, Credibook application awareness sessions, technical training on digital transaction recording, and an evaluation of changes in financial management. The training results showed that MSMEs managers were able to operate the application independently, with skills in recording daily transactions, managing accounts receivable and payable, monitoring inventory, and generating automated financial reports. The use of Credibook has proven to enhance operational efficiency and financial recording accuracy compared to previous conventional or manual methods. These findings indicate that digitalizing bookkeeping through a simple application can be an effective solution in promoting the growth and sustainability of SMEs, particularly in the traditional food industry sector.